The association between coffee consumption and type 2 diabetes in women - Chen, Mengjia (SFU Health Sciences Undergraduate Journal, 2022)
Diabetes is a worldwide chronic disease that affected many people’s lives, it is a preventable disease that has a great association with people’s lifestyles and diets. Coffee was a common beverage that emerged in people’s lives and was favoured by many people. With the popularity of coffee, the health effects of drinking coffee are also taken into account in many research studies. The article investigates whether the consumption of coffee will reduce the risk of Type 2 diabetes among women to fill the gap of specific sex studies. Three studies were examined and compared to support the idea that coffee consumption lowered the risk of type two diabetes in women.